PENGARUH ARUS KAS OPERASIONAL, AKRUAL, dan LEVERAGE TERHADAP PERSISTENSI LABA DENGAN BOOK TAX DIFFERENCES SEBAGAI MODERASI - Vidia Lia Rizky; Stefanus Dimas Ryan (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2025)
This study was conducted with the aim of examining the effect of operational cash flow, accrual, and leverage on profit persistence with BTD as moderation. This study used a sample of 55 manufacturing companies from the industrial sector listed on S&P Capital IQ and IDX for the 2020-2023 period with a purposive sampling technique. Data was collected using documentation techniques sourced from secondary data. Data processing using SPSS 29. This study found that partially operational and accrual cash flow had a negative effect on profit persistence. Meanwhile, leverage has a positive effect on profit persistence. In addition, this study also found that BTD strengthen the relationship between operating cash flow and profit persistence, book tax differences also strengthen the relationship between leverage and profit persistence. However, BTD do not strengthen the relationship between accruals and profit persistence. The results of these findings have relevant implications for academics and practitioners, namely adding to academic literature,providing a basis and reference for subsequent research to explore factors that have not yet been revealed. The results of this study can provide guidance for business practitioners in making decisions related to investment and better accounting policies to maintain financial performance stability in the long term.